Strategic Vector of Training Business Analysts in the Conditions of New National Priorities of Higher Education - N. A. Kazakova (Учёт. Анализ. Аудит)
The purpose of the article is to consider current problems of forming a strategy for the development of master’s programs for training business analysts in the context of new national priorities of higher education. To implement it, various scientific approaches and methods were used, including abstraction, analysis, synthesis, comparison and generalization of best practices, which made it possible to formulate modern requirements for the profession of business analyst as a provider of changes in the business environment. The identified factors, trends and staffing needs served as a guide for new approaches to improving the competency-based model of training business analysts, creating a request for the development of a project approach to training, as well as the interdisciplinarity of the business analysis methods used. The article presents the author’s approach to creating a program development strategy, as well as to the formation of a Partnership of interested organizations that are the «carriers» of competencies, regular monitoring of which will serve as a navigator for improving the competency-based model of training young personnel in the future. The approaches, experience and recommendations of the author used can be useful to academic leaders of master’s programs at universities, as well as in improving programs for advanced training and professional development of the youth.